Withholding Recognized Effective Adjuvant Anti-Neoplastic Chemotherapy in a Setting with Known Highly Active Treatment for Recurrent Disease: A Case Report - Maurie Markman (Case Reports in Oncology, 2010)
A young woman presenting with an ovarian immature teratoma (stage IA, grade 2) demonstrates the dilemma associated with the decision to withhold adjuvant chemotherapy of documented clinical utility in a setting where highly effective treatment is available should the cancer ultimately recur.